Diphosphonates and polyphosphates in medicine - Russell, R (1975)
Compounds containing phosphorus with P O P bonds (for example PPi) or P C P bonds (diphosphonates) bind strongly to crystals of hydroxyapatite and inhibit their growth and aggregation as well as their rates of dissolution. Both groups of compounds inhibit experimentally induced ectopic calcification in animals. The diphosphonates, which are more stable than PPi, also inhibit bone resorption and bone turnover in various experimental systems; PPi occurs naturally in body fluids and mineralized tissues and may have a physiological function regulating calcification and bone turnover. Abnormalities of PPi metabolism may occur in some human diseases, notably hypophosphatasia and pseudogout. EHDP is able to inhibit ectopic calcification in man, particularly in MOP. It also reduces excessive bone turnover in Paget's disease and excessive bone loss in some types of osteoporosis. 99mTc complexes of EHDP, PPi, and other polyphosphates have recently been used successfully as bone scanning agents. Diphosphonates are therefore not only interesting pharmacological agents for studies of calcium metabolism but are also potentially useful in the investigation and treatment of skeletal disorders in man.